Patch testing in fixed drug eruptions: a 20-year review. - Andrade, P (2012)
BACKGROUND: The fixed drug eruption is a common adverse drug reaction. Clear identification of the culprit drug is not always possible in the clinical setting, and oral rechallenge may induce new lesions or severe reactions. OBJECTIVES: The main purpose of this study was to evaluate the diagnostic value of patch testing in establishing an aetiological diagnosis in fixed drug eruptions. METHOD: A retrospective analysis was conducted evaluating 52 patients (17M/35F, mean age 53±17 years) with clinical diagnoses of fixed drug eruptions submitted to patch tests in a 20-year period in a Dermatology Department. Nonsteroidal anti-inflammatory drugs (NSAID) were clinically suspected in 90.4% of the cases, followed by antibiotics (28.9%) and paracetamol (15.4%). RESULTS: Patch tests on pigmented lesions were reactive in 21 patients (40.4%), 20 of those to NSAID (nimesulide, piroxicam and etoricoxib) and 1 to an antihistamine (cetirizine). All patch tests using other drugs were negative, even under conditions of high clinical suspicion. Oral rechallenge allowed confirmation of drug imputability in 5 of 31 test-negative cases. Cross reactivity was frequently observed between piroxicam and other oxicams, and between different antihistamines. CONCLUSIONS: Patch testing was shown to be a simple and safe method to confirm drug imputabililty in fixed drug eruption, mainly when NSAID or multiple drugs are suspected. Persistent lack of reactivity to drug classes such as antibiotics and allopurinol represent an important limitation